2019
DOI: 10.12659/msm.916064
|View full text |Cite
|
Sign up to set email alerts
|

Homo Sapiens Circular RNA 0079993 (hsa_circ_0079993) of the POLR2J4 Gene Acts as an Oncogene in Colorectal Cancer Through the microRNA-203a-3p.1 and CREB1 Axis

Abstract: Departmental sources Background: Worldwide, dietary changes have resulted in an increased incidence of colorectal cancer (CRC). Circular RNAs (circRNAs) are involved in tumorigenesis of several human tumors, but their role in CRC remains unknown. This study aimed to investigate the expression and effects of Homo sapiens (hsa)_circ_0079993 of POLR2J4 and its impact on CRC. Material/Methods: Paired CRC tissue and adjacent normal colorectal tissue samples (N=41), and HCT116 and SW620 human CRC cells were studied.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…For instance, Lu et al found that circ_0079993 promoted the progression of CRC through miR-203a-3p.1/CREB1 axis. 21 Yang et al reported that miR-101 restrained the proliferation and migration of CRC cells through down-regulating CREB1. 22 Nevertheless, the underlying mechanism by which CREB1 accelerating carcinogenesis of CRC is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Lu et al found that circ_0079993 promoted the progression of CRC through miR-203a-3p.1/CREB1 axis. 21 Yang et al reported that miR-101 restrained the proliferation and migration of CRC cells through down-regulating CREB1. 22 Nevertheless, the underlying mechanism by which CREB1 accelerating carcinogenesis of CRC is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…CircRNA has been reported to regulate CRC process. 29,30 Therefore, exploring the regulatory mechanism of CRC by circRNAs is necessary to search drug in treating CRC. CircRNAs were unveiled to mainly act as a carcinogen in CRC progression.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that circRNA molecules are rich in miRNA binding sites, which play the role of miRNA sponge in cells, thereby relieving the inhibition of miRNA on its target genes and increasing the expression level of target genes, this mechanism is called ceRNA mechanism 40 43 . circRNAs plays an important regulatory role in diseases through the interaction of miRNAs associated with diseases 44 , 45 . Hsa_circRNA_0068871, as the sponge of miR-181a-5p, can target and regulate the expression of FGFR3, activate STAT3 and promote the development of bladder cancer, which can be used as a potential biomarker 46 .…”
Section: Discussionmentioning
confidence: 99%